Atratividade e decisão: estudo exploratório sobre a influencia da atratividade no processo decisório em grupo - Moura, Wilson (1978)
This dissertation is concerned with the nature of the performance of human groups in relation to other variables considered relevant. Taking as a starting point theories that try to explain the nature, origin and functioning of human groups, mainly the ones of Freud, Moreno, Sartre, Lewin and the decision-making theory of Collins and Guetzkow, Davis and Jay Hall, this research was planned to analyse the behavior of the independent variable level of previons attraction existing among the members of a group during a decision-making process. Surprisingly, the results were completely different from the expected. However, through the qualitative analysis and subsequent quantitative empirical verification of the collected data, is was possible, in terms of a true 'serehdipity' to obtain a new and inexpected resu1t: the level of attraction was not responsible for the relative 'ideology rigidity' of the group, instead, it was found that it was responsible for the liberation of criativity among the members of the group. A factor that was extremely favourable to the research was the uniformity - that we have not expected and, initially, we dit not want - of the average potential of information available, as well as the average of intelligence and the group performance. So, as these sources of variations were constant during the research, it was possible, in the phase of research reformation, to turn them into 'intervenient variables', making explicit the dependence of the 'synergetic effect' when confronted with the level of attraction.